Structure-based design of native-like HIV-1 envelope trimers to silence non-neutralizing epitopes and eliminate CD4 binding. Issue 1 (December 2017) - Kulp, Daniel; Steichen, Jon; Pauthner, Matthias; Hu, Xiaozhen; Schiffner, Torben; Liguori, Alessia; Cottrell, Christopher; Havenar-Daughton, Colin; Ozorowski, Gabriel; Georgeson, Erik; Kalyuzhniy, Oleksandr; Willis, Jordan; et al.
Abstract Elicitation of broadly neutralizing antibodies (bnAbs) is a primary HIV vaccine goal. Native-like trimers mimicking virion-associated spikes present nearly all bnAb epitopes and are therefore promising vaccine antigens. However, first generation native-like trimers expose epitopes for non-neutralizing antibodies (non-nAbs), which may hinder bnAb induction. We here employ computational and structure-guided design to develop improved native-like trimers that reduce exposure of non-nAb epitopes in the V3-loop and trimer base, minimize both CD4 reactivity and CD4-induced non-nAb epitope exposure, and increase thermal stability while maintaining bnAb antigenicity. In rabbit immunizations with native-like trimers of the 327c isolate, improved trimers suppress elicitation of V3-directed and tier-1 neutralizing antibodies and induce robust autologous tier-2 neutralization, unlike a first-generation trimer. The improved native-like trimers from diverse HIV isolates, and the design methods, have promise to assist in the development of a HIV vaccine. Eliciting broadly neutralizing antibodies (bnAbs) is a primary HIV vaccine goal, but available immunogens expose epitopes for development of non-nAbs. Here, the authors use computational and structure-guided design to develop improved native-like envelope trimers and analyze Ab response in animal models.